Current Indications and Techniques for the Use of Bowel Segments in Pediatric Urinary Tract Reconstruction - Stein, Raimund; Zahn, Katrin; Huck, Nina (Frontiers in Pediatrics, 2019)
Abstract Today, there are only few indications for the use of bowel in pediatric urology. Due to the successful conservative therapy in patients with neurogenic bladders using clean intermittent catheterisation and pharmacotherapy as well as the established concept of primary reconstruction of the lower urinary tract in patients with the bladder exstrophy-epispadias complex, the indication for the use of bowel during early childhood has been extremely reduced. Only after the failure of the maximu conservative therapy or the failure of the primary reconstruction, bladder augmentation or urinary diversion should be considered. Malignant tumors of the lower urinary tract (e.g. rhabdomyosarcomas of the bladder/prostate) are another rare indication for urinary diversion. Replacement or reconstruction of the ureter with a bowel segment is also a quite rarely performed procedure. In this review, the advantages and disadvantages of the different options for the use of bowel segments for bladder augmentation, bladder substitution, urinary diversion or ureter replacement during childhood and adolescence are discussed.